“Xaste Nabâši(D)” As A Culture Specific Speech Act In Persian - Moghaddam, Masoume Khodaei; Elyasi, Mahmoud; Sharifi, Shahla (JOURNAL OF ADVANCES IN LINGUISTICS, 2014)
As different cultures have different speech acts and some cases of unsuccessful communication are due to the differences among the cultural patterns of speech acts, knowledge of these speech acts can help people to communicate more successfully. In this regard, the present paper ,based on Brown and Levinson Politeness Theory (1987), examines and analyzes œxaste nabi(d) speech act in Persian language to come up with the functions it serves in the Iranian Persian-speaking community for those non-Persian speakers who want to speak or learn Persian. For this purpose, some native speakers of Persian language from different ages and different groups were observed in such natural settings as markets, shops, the streets, and parties and their speech was recorded; then transcribed and translated into English, finally, the data was analyzed qualitatively. The results show that, there are seven major functions of xaste nabi(d) in Persian which are as follows: In literal meaning of "not being exhausted or tired", phatic communication, greeting and sometimes to bid farewell, mitigating request, to state indirectly end of a work or an activity, thanking and blaming. Finally, it is worth noting that we can define politeness in Persian language as using such politeness expressions (â€xaste nabi(d) not only for mitigating face threatening act (FTA), but also for face enhancing act (FEA) and successful interaction and communication. So incompatible with politeness definition of Brown and Levinson (1987) who consider politeness simply as a means of mitigating FTA, politeness in Persian is defined as FEA too.